Effectiveness of training prescription guided by heart rate variability versus predefined training for physiological and aerobic performance improvements: a systematic review and meta-analysis (2020)
A systematic review and meta-analysis were performed to determine if heart rate variability-guided training (HRV-g), compared to predefined training (PT), maximizes the further improvement of endurance physiological and performance markers in healthy individuals. This analysis included randomized controlled trials assessing the effects of HRV-g vs. PT on endurance physiological and performance markers in untrained, physically active, and well-trained subjects. Eight articles qualified for inclusion. HRV-g training significantly improved maximum oxygen uptake (VO2max) (MD = 2.84, CI: 1.41, 4.27; p < 0.0001), maximum aerobic power or speed (WMax) (SMD = 0.66, 95% CI 0.33, 0.98; p < 0.0001), aerobic performance (SMD = 0.71, CI 0.16, 1.25; p = 0.01) and power or speed at ventilatory thresholds (VT) VT1 (SMD = 0.62, CI 0.04, 1.20; p = 0.04) and VT2 (SMD = 0.81, CI 0.41, 1.22; p < 0.0001). However, HRV-g did not show significant differences in VO2max (MD = 0.96, CI −1.11, 3.03; p = 0.36), WMax (SMD = 0.06, CI −0.26, 0.38; p = 0.72), or aerobic performance (SMD = 0.14, CI −0.22, 0.51; p = 0.45) in power or speed at VT1 (SMD = 0.27, 95% CI −0.16, 0.70; p = 0.22) or VT2 (SMD = 0.18, 95% CI −0.20, 0.57; p = 0.35), when compared to PT. Although HRV-based training periodization improved both physiological variables and aerobic performance, this method did not provide significant benefit over PT.